2015
DOI: 10.1103/physreve.92.062715
|View full text |Cite
|
Sign up to set email alerts
|

Polymer ejection from strong spherical confinement

Abstract: We examine the ejection of an initially strongly confined flexible polymer from a spherical capsid through a nanoscale pore. We use molecular dynamics for unprecedentedly high initial monomer densities. We show that the time for an individual monomer to eject grows exponentially with the number of ejected monomers. By measurements of the force at the pore we show this dependence to be a consequence of the excess free energy of the polymer due to confinement growing exponentially with the number of monomers ini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…t w (s) is defined as the time it takes for a monomer labeled s to translocate after the previous monomer s − 1 has translocated. From our simu- * Author to whom correspondence should be addressed: riku.linna@aalto.fi lations using a hybrid method consisting of molecular dynamics (MD) and stochastic rotation dynamics (SRD) [11,12] we obtained t w that grows essentially exponentially with s [13].…”
Section: Introductionmentioning
confidence: 99%
“…t w (s) is defined as the time it takes for a monomer labeled s to translocate after the previous monomer s − 1 has translocated. From our simu- * Author to whom correspondence should be addressed: riku.linna@aalto.fi lations using a hybrid method consisting of molecular dynamics (MD) and stochastic rotation dynamics (SRD) [11,12] we obtained t w that grows essentially exponentially with s [13].…”
Section: Introductionmentioning
confidence: 99%
“…Using our general simulation model, we will study the ejection process for polymers of different bending rigidity. In our previous studies on capsid ejection of flexible polymers we showed that the ejection dynamics is governed by the force the polymer beads inside the capsid exert on the bead at the pore entrance [14,15]. As will be seen, this result cannot be generalized to semiflexible polymer chains.…”
Section: Introductionmentioning
confidence: 93%
“…As κ increases, there is a transition from exponential increase of t with s [14,15] to a regime where perfect scaling of t ∼ s 1.33 emerges for the main part of the ejection. This transition has the characteristics of a dynamical phase transition, where κ acts as a control parameter.…”
Section: E Cumulative Waiting Times: Cross-over To Scalingmentioning
confidence: 99%
See 2 more Smart Citations